Using standardized patients to assess the quality of type 2 diabetes care among primary care providers and the health system: Evidence from rural areas of western China - Wu, Yuju; Ye, Ruixue; Sun, Chang; Meng, Sha; Cai, Zhengjie; Li, Linhua; Sylvia, Sean; Zhou, Huan; Pappas, Lucy; Rozelle, Scott (Frontiers in Public Health, 2022)
Background Improving type 2 diabetes (T2D) care is key to managing and reducing disease burden due to the growing prevalence of diabetes worldwide, but research on this topic, specifically from rural areas, is limited. This study uses standardized patients (SPs) to assess T2D care quality among primary care providers to access the healthcare system in rural China. Methods Using multi-stage random sampling, health facilities, providers, and households were selected. SPs were used to evaluate providers' T2D care quality and a questionnaire survey was used to collect patient sorting behaviors from households. Logistic regression was used to explore factors correlated with T2D care quality. Provider referral and treatment rates were combined with patient sorting behaviors to assess the overall quality of T2D management by rural China's healthcare system. Results A total of 126 providers, 106 facilities, and 750 households were enrolled into this study. During SP interactions, 20% of rural providers followed the national guidelines for T2D consultation, 32.5% gave correct treatment, and 54.7% provided lifestyle suggestions. Multi-variable regression results showed that providers who had earned practicing certificates (β = 1.56, 95% CI: 0.44, 2.69) and saw more patients (β = 0.77, 95%: 0.25, 1.28) were more likely to use a higher number of recommended questions and perform better examinations, whereas providers who participated in online training were less likely to practice these behaviors (β = −1.03, 95%: −1.95, −0.11). The number of recommended questions and examination (NRQE) was the only significant correlated factor with correct treatment (marginal effect = 0.05, 95%: 0.01, 0.08). Throughout the rural healthcare system, 23.7% of T2D patients were treated correctly. Conclusion The quality of T2D care in rural western China, especially throughout the consultation and treatment process during a patient's first visit, is poor. Online training may not improve T2D care quality and low patient volume was likely to indicate poor care quality. Further research is needed to explore interventions for improving T2D care quality in rural China's healthcare system.